Psychological status of women with miscarriage - I. A. Salov; I. V. Naumova; A. V. Parshin; M. V. Lomovitskaya (Акушерство, гинекология и репродукция, 2024)
Introduction. During pregnancy, a woman becomes vulnerable to develop symptoms of depression and anxiety, which in turn are associated with increased risk of perinatal complications, postpartum depression as well as behavioral problems in children.Aim: to assess the prevalence of symptoms related to depression and anxiety in pregnant women with threatened abortion (ТА), non-developing pregnancy (NP) as well as those with physiological course of pregnancy (РР) in the first trimester of pregnancy; to reveal major predictors of psycho-emotional disorders in pregnant women.Materials and Methods. Three groups of pregnant women were stratified: 62 patients with TA, 60 patients with NP and 57 women with PP. Clinical history and physical examination were performed in all subjects. All pregnant women were assessed by Hamilton Anxiety Rating Scale and the Beck Depression Inventory.Results. It was found that the mean Beck’s score was significantly higher in NP vs. TA and PP groups (p < 0.05). Moreover, significant differences were also observed while comparing TA and PP groups (p = 0.037). Clinically important depression was found in 3.3 % NP women and in 1.6 % TA women. Preclinical depression was found in 13 % and 6.5 % women with NP and TA, respectively. The mean Hamilton scale score was significantly higher in NP vs. PP group (p < 0.05), but was comparable with that in TA group (p > 0.05). The mean score on the anxiety scale was significantly higher in TA vs. PP group (p = 0.001). Clinically significant mild to moderate anxiety was found in 4.9 % and 1.6 % TA and NP women, respectively. Mild anxiety symptoms were noted in 35.5 % of women with TA, 38.3 % of women with NP, and 15.7 % of women with PP. Multiple linear regression analysis revealed that a burdened obstetric history and the duration of the patient hospital stay had the strongest association with symptoms of depression and anxiety.Conclusion. Symptoms of prenatal anxiety and depression are widespread and should be identified in a timely manner. Psychological counseling and testing of pregnant women should be included into recommendations for pregnancy management.